Estimating crop coefficients for corn during an evapotranspiration experiment on an oxisol in Brazil (Scientia Agricola, 1994)
Soil water balance components were measured during two periods (from 1989 to 1991) on a Dark Red Latosol (oxisol) in Piracicaba,SP, Brazil. The change in soil water storage and the soil water fluxes at the lower limit of the rooting zone were calculated for a transect of 25 observation plots. Hydraulic head gradients were determined by tensiometer measurements. Soil water flux densities were estimated through Darcy's equation. The actual evapotranspiration of the crops and weeds and the actual evaporation of bare soil were obtained from the water balance equation and this for two periods under different crop rotations. For the first period the sequence was bare soil-corn-weeds and for the second period it was stubble mulch-weeds-corn. For assessing the crop coefficients the potential evapotranspiration was calculated according to two different methods. The first method was based on the modified Penman equation with grass as a reference crop, to obtain this way reference coefficients, and the second method was based on the pan "A" evaporation data in order to obtain pan coefficients. These coefficients were compared with the tabulated crop coefficients. In general when there was no shortage of water during the corn growth, the crop coefficients k c"A" and k c ref were very close to the k c values.